'Our city of love and of slaughter': Berlin klezmer and the politics of place. Issue 1 (2nd January 2018) - Alexander, Phil
ABSTRACT: Although it claims little historical connection to klezmer music or Yiddish culture, the city of Berlin has hosted one of the most dynamic klezmer scenes of the past 20 years. This article analyses ways that place has been made to function as a meaningful unit in the music and lyrics of several artists living and working in Berlin, localising the transnational klezmer revival discourse by rooting the city in their music. Building on Adam Krims' theory of 'urban ethos', I explore how the contemporary city is emplaced in its klezmer music, arguing that these processes of signification allow us to hear contrasting articulations of Berlin. The native Berliners ?Shmaltz! frame their city as an escapist gateway, the American songwriter Daniel Kahn sees a site of painfully unresolved history and the internationalist Knoblauch Klezmer band locate Berlin as an embodiment of playfully multilingual performativity.